A Study on Building Condition Assessment at Kluang High School (STK) - Nurul Syaffiqah Eliya Rahmat,; Nurdalila Saji, (Progress in Engineering Application and Technology, 2024)
This study emphasises the value of building condition assessment in preserving the built assets structural integrity, use, and safety. Different building components, such as structural element, mechanical and electrical systems, architectural aspects, and overall performance are all evaluated throughout the evaluation process. This way, the authorities can decide on maintenance, repairs, and renovations to ensure the building has the best possible lifetime and functionality by conducting inspection. This study take place at Kluang High School (STK), Kluang, Johor. It is quite acceptable for the building to be assessed given that it is now 84 years old. For proactive asset management and extending infrastructure lifespan, effective building condition assessment practises are crucial. The objective of this study are to identify the type of defects that occur on building elements, to evaluate the building condition and to compare the method of building condition assessment which is Condition Survey Protocol (CSP 1) and the Portuguese method. The results of this study shown that the building are still in good condition even some of the building parts look old. The Condition Survey Protocol (CSP 1) matrix and the Portuguese Method were both employed in this study as the research methods. The data obtained are gathered and compared to determine the best and most reliable approach to be used in building condition assessment process.